2019
DOI: 10.1155/2019/8262849
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Are More Effective Than Their Extracellular Vesicles at Reducing Lung Injury Regardless of Acute Respiratory Distress Syndrome Etiology

Abstract: Although mesenchymal stromal cells (MSCs) have demonstrated beneficial effects on experimental acute respiratory distress syndrome (ARDS), preconditioning may be required to potentiate their therapeutic effects. Additionally, administration of cell-free products, such as extracellular vesicles (EVs) obtained from MSC-conditioned media, might be as effective as MSCs. In this study, we comparatively evaluated the effects of MSCs, preconditioned or not with serum collected from mice with pulmonary or extrapulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…Nevertheless, compared to MSCs, MSC-conditioned media (administered intravenously) was unable to improve lung edema and inflammation, arterial oxygenation, or static compliance in a subsequent study conducted by the same group (Hayes et al 2015). Similar findings were observed in models of endotoxin-induced lung injury (Silva et al 2019a).…”
Section: Increased Alveolar Fluid Clearance and Lung Recoverymentioning
confidence: 54%
“…Nevertheless, compared to MSCs, MSC-conditioned media (administered intravenously) was unable to improve lung edema and inflammation, arterial oxygenation, or static compliance in a subsequent study conducted by the same group (Hayes et al 2015). Similar findings were observed in models of endotoxin-induced lung injury (Silva et al 2019a).…”
Section: Increased Alveolar Fluid Clearance and Lung Recoverymentioning
confidence: 54%
“…MSCs were more effective than EVs in reducing lung injury. Specifically, MSCs demonstrated superior ability to reduce neutrophil cell count, alveolar collapse, lung elastance, interstitial edema and fibrosis [151]. The safety of intravenous infusion of high dose (10 × 10 6 cells/kg body weight) BM-MSCs was also demonstrated in an ovine model of bacterial pneumonia [152].…”
Section: Preclinical Studies Of Msc Therapy In Acute Lung Injury (Ali)mentioning
confidence: 93%
“…Conforti et al discovered that MSC-EVs had a lower ability to modulate T cell proliferation and antibody formation than MSCs [36]. In models of LPSinduced lung injury, Silva et al reported that MSCs BM bone marrow, MSC-EVs mesenchymal stem cells-derived extracellular vesicles, miR microRNA, TLR4 toll-like receptor 4, HMGA2 high-mobility group A2, LPS/GalN lipopolysaccharide and D-galactosamine, GVHD graft versus host disease, NLRP3 NOD-, LRR-and pyrin domain-containing protein 3, TSG-6 tumor necrosis factor-α-stimulated gene-6, CCR2 C-C motif chemokine receptor-2, TLR Toll-like receptor, IFN-γ interferon gamma produced greater protection compared with MSC-EVs prepared from the same number of cells [37]. Compared with MSCs, MSC-EVs may confer several advantages.…”
Section: Msc-evsmentioning
confidence: 99%